TRANSFORMATION OF BANKING TRANSACTIONS THROUGH MOBILE APPS – AN EMPIRICAL STUDY IN CHANGING FINANCIAL ENVIRONMENT - Pallathadka, Harikumar; Pallathadka, Laxmi Kirana (The journal of contemporary issues in business and government, 2022)
The evolution of the banking sector has been affected by the development of the internet and mobile application technologies. With the increased use of mobile phones and the help of the Internet, virtually every area and business have changed. Using mobile apps for banking services and transactions refers to the provision of banking services with the help of mobile. The adoption of mobile applications to avail banking services has changed the banking system. It is proved successful, easy to use, and cost-effective by customers and the banking industry. Security, safety, and convenience are some of the significant factors on which mobile banking depends. At present, many customers have adopted mobile banking transaction systems. However, some customers still feel hesitant to use mobile applications to avail banking services. A sample of 122 respondents was collected through a "standard questionnaire," created on a five-point interval scale.